The growth and rooting dimensions of the Local and Solomon Albizia in the agroforestry system - NIKMATUL AZIZAH; NURHENI WIJAYANTO; DESTA WIRNAS (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Azizah N, Wijayanto N, Wirnas D. 2019. The growth and rooting dimensions of the Local and Solomon Albizia in the agroforestry system. Biodiversitas 20: 3018-3023. Albizia (Falcataria moluccana (Miq.) Barneby & J.W.Grimes) is one of the leguminous plants that has a fast-growing character and profitable wood. Some types of albizia such as local albizia and Solomon albizia are cultivated by the community. Albizia planting can be integrated with crops such as upland paddy in agroforestry systems. Research on albizia planted in the agroforestry system was conducted to analyze the growth and root dimensions. This research was conducted for six months at the Cikabayan Field, Faculty of Forestry, IPB University, Bogor, West Java. This study was composed of two activities, those : (i) analyzing the effect of the albizia provenance on the growth of diameter, height, and canopy area, (ii) analyzing the root dimensions in agroforestry systems. The results showed that the albizia provenance had significant effect fo diameter, height, canopy area, and root length variable. F1 Solomon albizia has the best growth in all measured variables. F1 Solomon albizia has differed significantly with F2 Solomon and local albizia.